ChemInform Abstract: High‐Pressure Synthesis, Crystal Structure, and Magnetic Properties of Sr2MnO3F: A New Member of Layered Perovskite Oxyfluorides. Issue 20 (April 2016) - Su, Yu; Tsujimoto, Yoshihiro; Matsushita, Yoshitaka; Yuan, Yahua; He, Jianfeng; Yamaura, Kazunari
Abstract: Sr2 MnO3 F is prepared by hot pressing and annealing of stoichiometric amounts of SrF2, SrO, and Mn2 O3 (Pt capsule in belt‐type high‐pressure cell, 6 GPa, 1800 °C, 45 min).